Clinicopathologic and prognostic significance of tumor-infiltrating CD8+ T cells in patients with hepatocellular carcinoma: A meta-analysis. Issue 2 (January 2019) - Xu, Xuezhong; Tan, Yulin; Qian, Yan; Xue, Wenbo; Wang, Yibo; Du, Jianguo; Jin, Lei; Ding, Wei
Abstract: Background: In patients with hepatocellular carcinoma (HCC), the clinicopathologic and prognostic roles of tumor-infiltrating CD8+ T cells for survival are still controversial. A meta-analysis was performed to resolve this issue. Methods: We identified studies from PubMed, Embase, and the Cochrane Library to evaluate the clinicopathologic and prognostic value of tumor-infiltrating CD8+ T cells in patients with HCC. A meta-analysis was conducted to estimate clinicopathologic characteristics, overall survival (OS), and disease-free survival. The hazard ratio (HR) and 95% confidence interval (CI) were calculated employing fixed-effect or random-effect models depending on the heterogeneity of the included trials. Results: A total of 3509 patients from 21 observational studies were enrolled. The meta-analysis revealed that high levels of intratumoral CD8+ tumor-infiltrating lymphocytes (TILs) were associated with better OS (OS; HR = 0.676, P = .001) and disease-free survival (disease-free survival [DFS]; HR = 0.712, P = .002). The pooled analysis also demonstrated high density of infiltration of CD8+ TILs in margin of tumor (MT) was statistically significant associated with better OS (HR = 0.577; P <.001). Moreover, the patients with low CD8+ TILs infiltration had negative HBSAg (OR = 1.67, P = .02), large tumor size (OR = 1.74, P <.01), and later TNM stage (OR = 1.70, P <.01). Conclusions: Our findings suggested that low levels of CD8+ TILs predict large tumor size, later TNM stage and might be a promising prognostic factor of HCC especially for Asian patients. High-quality randomized controlled trials are needed to determine if CD8+ TILs could serve as targets for immunotherapy in hepatocellular carcinoma.